The PR masterclass : how to develop a public relations strategy that works! - Singleton, Alex (Chichester, West Sussex, United Kingdom : Wiley, 2013)
"The PR Masterclass is written by former newspaper, magazine and digital journalist Alex Singleton, who is now a prominent PR trainer and consultant. It reveals the secrets of effective PR and shows how to put in place a practical, reliable and successful media strategy for your product, business or activity - one that delivers the greatest results. Through the book, you get to discover how to develop and pitch effective newsworthy material, regardless of your budget. The PR Masterclass is aimed at PR professionals as well as small business owners and entrepreneurs implementing a PR strategy."
The content of an article; Newspaper grammar; Proofreading; The most important word in the English language; The Flesch-Kincaid reading ease test; Promoting the article; Dealing with rejection; The problem with American newspaper columns; Chapter 8: The Secrets of Effective Television and Radio Appearances; Appearing on television; Appearing on radio; Your own radio studio; The pre-record; Don't be a robot; Start off small; Preparation; The snowball; Chapter 9: How to Choose an Agency or Consultant; How to select an agency; Audit your communications first.
Why trade association membership matters.
Includes bibliographical references and index.
Print version record.
Keywords: Public relations; Consultations; Public relations -- Great Britain; Public relations; BUSINESS & ECONOMICS -- Advertising & Promotion; Public relations; Electronic books; Electronic books